Volume 7: Fluids Engineering 2017
DOI: 10.1115/imece2017-72314
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Drag Reduction on Superhydrophobic Surfaces Using Quartz Crystal Microbalance (QCM)

Abstract: A durable superhydrophobic coating formulation with epoxy binder thermoset was used to coat on surfaces, which provide high quality for corrosion protection, reduced biofouling and improved hydrodynamic behavior. The single and double layers coating of these nanostructured epoxy were fabricated and coated on a novel quartz crystal microbalance (QCM) technique to investigate their hydrophobic properties. Different static and dynamic wettability were obtained and characterized by evaluating the electrical impeda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Similarly, a surface is called oleophilic when the contact angle made by low surface liquids like oil is less than 90°, while it is referred to as super oleophobic when the contact angle is greater than 150°. [ 12–17 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a surface is called oleophilic when the contact angle made by low surface liquids like oil is less than 90°, while it is referred to as super oleophobic when the contact angle is greater than 150°. [ 12–17 ]…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a surface is called oleophilic when the contact angle made by low surface liquids like oil is less than 90 , while it is referred to as super oleophobic when the contact angle is greater than 150 . [12][13][14][15][16][17] F I G U R E 1 Droplet configurations for (A) Young's relation, (B) the Wenzel state (homogenous interface) and (C) the Cassie-Baxter state (composite interface) [23] as well as (D) the effect of roughness factor (R f ) and intrinsic contact angle (θ 0 ) on the contact angle and the equilibrium contact angle (θ) for a rough surface as a function of roughness factor and f LA values on (E) a hydrophobic surface and (F) a hydrophilic surface. [19,22,24,25] (G) Schematic illustration of re-entrant or overhang structures required to repel low surface tension liquids.…”
Section: Introductionmentioning
confidence: 99%
“…The cumulative hydrodynamic and micropillar loading was considered, to reduce the Q factor or increase the dissipation energy. Other researchers worked on the effect of the wetting state of liquids on the micropillars [ 15 , 16 , 17 , 18 , 19 , 20 ]. Their experimental results demonstrated that the wetting state and the micropillar’s height significantly affect the frequency shift of the QCM.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest is the fabrication of polystyrene shells coated by a polyvinyl alcohol layer (PS-PVA double-layer shells), adopted as a fuel container in ICF experiments [8], which are made up of PS shells, used as the supporting base, and the PVA outer layer serving as a gas-barrier. Besides, the coating of polymethyl methacrylate (PMMA) polymer on a quartz crystal microbalance (QCM) sensor operating in water also shows many applications, such as drag reduction, biological and condensation measurements [9][10][11][12][13]. Generally, such PS-PVA double-layer shells are usually prepared by solidifying the integrated S/W/O compound droplets.…”
Section: Introductionmentioning
confidence: 99%